Cellular and Molecular Responses of Dunaliella tertiolecta by Expression of a Plant Medium Chain Length Fatty Acid Specific Acyl-ACP Thioesterase - Lin, Huixin; Shen, Hui; Lee, Yuan K. (Frontiers in Microbiology, 2018)
Metabolic engineering of microalgae to accumulate high levels of medium chain length fatty acids (MCFAs) has met with limited success. Traditional approaches employ single introduction of MCFA specific acyl-ACP thioesterases (TEs), but our current research in transgenic Dunaliella tertiolecta line has highlighted that, there is no single rate-limiting approach that can effectively increase MCFA levels. Here, we explore the accumulation of MCFAs in D. tertiolecta after transgenic expression of myristic acid biased TE (C14TE). We observe that the MCFA levels were negatively correlated to the fatty acid (FA) synthesis genes, ketoacyl-ACP synthase II (KASII), stearoyl-CoA-9-desaturase (Δ9D), and oleoyl-CoA-12-desaturase (Δ12D). To further examine the molecular mechanism of MCFA accumulation in microalgae, we investigate the transcriptomic dynamics of the MCFA producing strain of D. tertiolecta. At the transcript level, enhanced MCFA accumulation primarily involved up-regulation of photosynthetic genes and down-regulation of genes from central carbon metabolic processes, resulting in an overall decrease in carbon precursors for FA synthesis. We additionally observe that MCFA specific peroxisomal β-oxidation gene (ACX3) was greatly enhanced to prevent excessive build-up of unusual MCFA levels. Besides, long chain acyl-CoA synthetase gene (LACS) was down-regulated, likely in attempt to control fatty acyl supply flux to FA synthesis cycle. This article provides a spatial regulation model of unusual FA accumulation in microalgae and a platform for additional metabolic engineering targeting pathways from FA synthesis, FA transport, and peroxisomal β-oxidation to achieve microalgae oils with higher levels of MCFAs.